1989
DOI: 10.1111/j.1399-3054.1989.tb05617.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin concentration in relation to mineral nutrition and benzyladenine treatment in Plantago major ssp. pleiosperma

Abstract: Cytokinins in shoot and root tissue were studied in plants of Plantago major L. ssp. pleiosperma (Pilger) grown on a concentrated and on a dilute nutrient solution. Cytokinins of plants transferred from the concentrated to the dilute solution were compared with plants treated similarly but with 10−8M benzyladenine (BA) added to the dilute solution. Cytokinin concentrations were also measured in plants that had been grown throughout on one of the two nutrient solutions. A restricted supply of minerals was corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
0
9

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 42 publications
8
48
0
9
Order By: Relevance
“…Cytokinin acts stimulating chloroplast development and maintenance (SALISBURY & ROSS, 1992). Similar results have been observed in plants grown under nutritional deficient solution containing cytokinin, where the nutritional deficiency symptoms were alleviated (KUIPER et al, 1989). At the other fertilizer concentrations, P SAG12 -ipt lines had a similar amount of chlorophyll in leaves as wild-type plants ( Table 2).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Cytokinin acts stimulating chloroplast development and maintenance (SALISBURY & ROSS, 1992). Similar results have been observed in plants grown under nutritional deficient solution containing cytokinin, where the nutritional deficiency symptoms were alleviated (KUIPER et al, 1989). At the other fertilizer concentrations, P SAG12 -ipt lines had a similar amount of chlorophyll in leaves as wild-type plants ( Table 2).…”
Section: Resultssupporting
confidence: 74%
“…Cytokinin exogenous applications alleviate symptoms of restricted mineral supply (KUIPER et al, 1989;HARE et al, 1997). The plant gene that encodes the first enzyme involved in the cytokinin synthesis process has not been identified yet; however, an Agrobacterium tumefaciens gene that encodes the same enzyme was identified and isolated, the isopentenyl transferase (ipt) gene (GAN & AMASINO, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Root tips, as sites of cytokinin pro duction, react rapidly upon alterations in mineral supply. Work with various plant species showed that a reduction in mineral supply to the root tips induced a decrease in internal cytokinin concentrations in roots, shoots and xylem sap (Kuiper et al 1989 and references herein). The strongest reductions in cyto kinin levels were induced by nitrogen, the effects of phosphate were less pronounced (Coleman et al 1990).…”
Section: Germinationmentioning
confidence: 99%
“…Although these views do not imply direct roles for plant hormones, it is well known that changes in N availability strongly affect hormone levels, with cytokinins as a prime example. Cytokinin concentrations of roots, shoots, and xylem sap decrease at low N supply (10,12,26,29), and a role for cytokinins from roots in the control of R:T at nutrient limitation has been suggested (12)(13)(14). Exogenous application of cytokinins delay the growth retardation caused by N limitation (12,13,29).…”
mentioning
confidence: 99%
“…Cytokinin concentrations of roots, shoots, and xylem sap decrease at low N supply (10,12,26,29), and a role for cytokinins from roots in the control of R:T at nutrient limitation has been suggested (12)(13)(14). Exogenous application of cytokinins delay the growth retardation caused by N limitation (12,13,29). Cytokinins are also important moderators during lateral root initiation, whereas auxin is considered promotive (30).…”
mentioning
confidence: 99%